EFFECTIVENESS OF COOPERATION, CRITERIA AND INDICATORS FOR ITS EVALUATING - MIRAKIN, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the effectiveness of cooperative activities in the agricultural sector. The main attention is paid to the analysis of criteria and indicators that allow to evaluate the efficiency of cooperation at different levels - from individual cooperatives to the national cooperative system. The economic, social and organizational aspects of the functioning of cooperatives are analyzed, emphasizing the importance of integrating different approaches to evaluating their activities. The article pays special attention to the development of a system of indicators that take into account the specifics of agricultural cooperation, in particular, its role in ensuring economic stability, increasing labor productivity, social cohesion and the development of rural areas. It was also emphasized the need to take into account environmental criteria in the process of evaluating the effectiveness of cooperation, which is of particular importance in the context of global climate change and increased requirements for sustainable development. The article offers methodological approaches to the comprehensive evaluation of the effectiveness of cooperation, which can be used as a basis for developing strategies for the development of the cooperative movement in Ukraine. Analyzing the existing approaches to the assessment of efficiency, key directions for further research are identified, in particular, the study of the influence of state support on the development of cooperatives, optimization of the organizational structure of cooperative associations, and the development of innovative approaches to managing cooperatives. The article examines various approaches to the concept of "efficiency", existing methods of assessing and calculating efficiency both on a quantitative and qualitative basis; the methods of assessing the effectiveness of interfirm cooperation are analyzed. The formula for calculating the effectiveness of types of cooperation is presented, which can be used both for comparing cooperative associations and as a component indicator when deciding to participate in cooperation. The need to increase the efficiency and improve the management system of its activities is of particular importance in ensuring the sustainable pace of development of the agricultural cooperative and the active implementation of the social mission. Therefore, the study of the problems of evaluation and improvement of the effectiveness of cooperation organizations in the field of agriculture is relevant.
Keywords: cooperation; efficiency; efficiency evaluation method; profitability; cooperative policy